Cultural Preferences and Firm Financing Choices - Bedendo, Mascia; Garcia-Appendini, Emilia; Siming, Linus (Journal of Financial and Quantitative Analysis, 2020)
We document significant differences in the financing structures of small firms with managers of diverse cultural backgrounds. To isolate the effect of culture, we exploit cultural heterogeneity within a geographical area with shared regulations, institutions, and macroeconomic cycles. Our findings suggest significant cultural differences in the preference toward debt funding and in the use of formal and informal sources of financing (bank loans and trade credit). Our results are robust to alternative explanations based on potential differences in credit constraints and in the distribution of cultural origins across industries, trading partners, and headquarters locations.